The influence of burnout on cardiovascular disease: a systematic review and meta-analysis - John, Awena; Bouillon-Minois, Jean-Baptiste; Bagheri, Reza; Pélissier, Carole; Charbotel, Barbara; Llorca, Pierre-Michel; Zak, Marek; Ugbolue, Ukadike C.; Baker, Julien S.; Dutheil, Frederic (Frontiers in Psychiatry, 2024)
Background: Burnout is a public health problem with various health consequences, among which cardiovascular disease is the most investigated but still under debate. Our objective was to conduct a systematic review and meta-analysis on the influence of burnout on cardiovascular disease.Methods: Studies reporting risk (odds ratio, relative risk, hazard ratio) of cardiovascular disease following burnout were searched in PubMed, PsycInfo, Cochrane, Embase, and ScienceDirect.We performed a random-effect meta-analysis stratified by type of cardiovascular disease and search for putative influencing variables. We performed sensitivity analyses using the most adjusted models and crude risks.We included 25 studies in the systematic review, and nine studies in the meta-analysis (four cross-sectional, four cohort, and one case-control study) for a total of 26 916 participants.Burnout increased the risk of cardiovascular disease by 21% (OR=1.21, 95CI 1.03 to 1.39) using the most adjusted risks and by 27% (OR=1.27, 95CI 1.10 to 1.43) using crude risks. Using stratification by type of cardiovascular disease and the most adjusted risks, having experienced burnout significantly increased the risk of prehypertension by 85% (OR=1.85, 95CI 1.00 to 2.70), and cardiovascular disease-related hospitalization by 10% (OR=1.10, 95CI 1.02 to 1.18); whereas the risk increased for coronary heart disease (OR=1.79, 95CI 0.79 to 2.79) and myocardial infarction (OR=1.78, 95CI 0.85 to 2.71) were not significant. Results were also similar using crude odds ratio. The risk of cardiovascular disease after a burnout was not influenced by gender. Insufficient data precluded other meta-regressions.Burnout seems to increase the risk of cardiovascular disease, despite the few retrieved studies and a causality weakened by cross-sectional studies. However, numerous studies focused on the pathophysiology of cardiovascular risk linked with burnout that may help to build preventive strategy in the workplace.